ANALISIS PUTUSAN BEBAS TERHADAP PENYALAHGUNAAN NARKOTIKA (Studi Kasus Putusan Pengadilan Negeri Bengkayang Nomor 45/Pid.B/2011/BKY dan Nomor 46/Pid.B/2011/BKY) - FAJAR DANI SUSANTO, S.Ik. A.21210078, Jurnal Mahasiswa S2 UNTAN (Jurnal NESTOR Magister Hukum, 2014)
ABSTRACTThesis discusses the problem analysis Narcotics Abuse Verdict Against Free (A Case Study of State Court Decision Bengkayang 45/Pid.B/2011/Bky No. And No. 46/Pid.B/2011/Bky).From the results of research using normative legal research methods and Sociological , it is concluded that : ( 1 ) Basic considerations Bengkayang District Court judge dropped the acquittal of the accused in the case of drug abuse by Decision No: 45/Pid.B/2011/PN.BKY and Verdict no: 46/Pid.B/2011/PN.BKY is that the facts revealed in court is not enough evidence to convict the accused because criminal elements are not met , it is also based on the belief the judge that the defendant is not guilty of the crime charged to him , because all of the evidence presented at trial did not prove that the defendant committed the act of drug abuse as stipulated in Law No. 35 Year 2009 on narcotics . ( 2 ) . Prosecutors have difficulties to take legal actions against the acquittal where the defendant foreign stamps that have been out of the territory of Indonesia . Legal efforts can still be made but must cooperate with law enforcement officials accused the country of origin ( Malaysia ) , and it is hard to do because there is no agreement between the government of Indonesia and Malaysia .Recommendations in this thesis : ( 1 ) The use of narcotics is not for medical purposes and / or knowledge iimu is prohibited act , so it deserves to be punished for its misuse . The judge in making a decision it shall not only based on the rule of law ( legislation funnel ) , but also should pay attention to the values of law and justice that lives and grows in the community . ( 2 ) Given the development of the distribution and use of narcotics is not for medical and / or scientific equipment including Bengkayang increasing , then the law enforcement officers ( investigators , prosecutors , and judges ) should increase cooperation , so that the culprit can be the fairest punishment in accordance with the actions undertaken , in order to conduct drug abuse does not happen again and not widespread . ( 3 ) Given the impact of drug use are very large for human health and safety , then the participation of all stakeholders is needed to do the eradication and prevention ( preventive and repressive ) against drug abuse , in order to create security , order and peace in society .Key note: acquittal, penyalahgunaan dan bahaya narkoba,narcotics abuse